Developing a strength and conditioning technical framework: An example from a canoe slalom national performance program - Rawlley-Singh, I.; King, R. (Strength and Conditioning Journal, 2021)
Canoe slalom requires technical ability, well-developed energetics, a high level of maximum force production, and range of movement to perform a variety of complex paddle stokes, while maneuvering through a challenging whitewater course. The strength and conditioning (S&C) coach should provide strategic direction across a network or department including S&C coaches working toward identified outcomes and measures. S&C coaches should collaborate with a multidisciplinary support team (i.e., sport coaches, physiotherapists, physiologists, etc.) to develop a technical framework. The technical framework may allow for development of training strategies that provide a clear breakdown of the outcomes, adaptations, exercises, and testing methods. The current article articulates this process related to a canoe slalom national performance program.